Highly Efficient Glass Ceramic Thermal Insulation - Vedyakov Ivan (E3S Web of Conferences, 2021)
Alkali-silicate thermal insulation materials (foam silicates) belong to the group of mineral heat insulators. Their main disadvantage is insufficient water resistance, to increase which special water-strengthening additives are introduced into materials. The aim of this work was to obtain and study foam silicates in granular (FGCG) and slab (FGCS) forms using a new production technology characterized by a simple one-stage technological scheme. Natural or technogenic amorphous silica, glassy sodium silicate (with the addition of carbonate or hydroxide) and a carbon-containing foaming agent, were used as the raw materials. Some part of the silica component was included in the binder solution, which made it possible to increase the silicate modulus in the final product to 5-10. This factor together with rather high Al2O3 concentration in the silica raw, made it possible to obtain foamed materials of very high water resistance. Another feature of the applied technology was a high foaming temperature (750–900°C). This factor makes a significant contribution to improving the water resistance of foam silicates, and significantly reducing their thermal conductivity and water absorption. As a result, FGCG was obtained with a bulk density of 170-440 kg/m3 (for FGCS – 300-400 kg/m3), a compressive strength in a cylinder of 0.5-6.3 MPa, a thermal conductivity of 0.046-0.084 W/(m·K) and a water absorption of 7.8-13.5% by volume. Mass loss of the specimens in boiling water was 0.12-0.33%, which puts obtained foamed materials on a par with most waterproof foam silicates being produced today.